2003
DOI: 10.1063/1.1629378
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of a highly oriented, textured thin film of the ionic conductor Gd:CeO2−δ on (001) MgO

Abstract: Highly oriented ionic conductor gadolinium-doped CeO2−δ (Ce0.8Gd0.2O2−δ) thin films have been grown on single-crystal (001) MgO substrates by pulsed-laser ablation. The films are highly c-axis oriented with cube-on-cube epitaxy, as shown by x-ray diffraction and electron microscopy. The interface relationship is, surprisingly, found to be (001)film//(001)sub and [100]film//[100]sub with an extremely large lattice misfit of more than 28%. Ac impedance measurements in the temperature range of 500 to 800 °C revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 11 publications
4
53
1
Order By: Relevance
“…2009, 19, 1713-1719 ß 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim enhancement at low pO 2 can be attributed to electronic conductivity related to Ce reduction at low pO 2 . [13,14,18,34] The typical process of ceria reduction may be written as:…”
Section: Resultsmentioning
confidence: 99%
“…2009, 19, 1713-1719 ß 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim enhancement at low pO 2 can be attributed to electronic conductivity related to Ce reduction at low pO 2 . [13,14,18,34] The typical process of ceria reduction may be written as:…”
Section: Resultsmentioning
confidence: 99%
“…GDC films with a columnar structure and 170 nm thickness were epitaxially grown on MgO (001) single crystals by pulsed laser ablation [40]. The large lattice mismatch of 28.8% created various defects at the film/MgO interface, as verified by high-resolution transmission electron microscopy (HRTEM).…”
Section: Heterostructures Reduced At Minimum: Single Thin Filmsmentioning
confidence: 99%
“…Secondly, thin film technologies are employed to reduce the electrolyte thickness to the sub-µm level, as the ohmic resistance scales linearly with the thickness. However, it was shown that transport properties of thin ceria-based electrolytes depart vastly from bulk, microcrystalline materials [5][6][7][8][9][10][11][12][13]. For example, a wide range of conductivity levels (from 3.4 × 10 −6 S/cm [12] to 7 × 10 −3 S/cm [8] both at 500°C) and a significant variation of activation energy (from 0.81 eV [10] to 1.3 eV [9]) have been reported.…”
Section: Introductionmentioning
confidence: 99%